PENGARUH LABEL HALAL, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MEREK WARDAH DI KOTA LHOKSEUMAWE - Rika Saprianti; Nursanjaya Nursanjaya (Negotium: Jurnal Ilmu Administrasi Bisnis, 2021)
The goal of this study is to see how the halal label, product quality, and pricing affect purchase decisions. The halal label (X1), product quality (X2), and pricing were the independent factors in this study (X3). Purchasing decisions for Wardah brand cosmetics are the dependent variable in this study. This study used 80 respondents from the Wardah consumer population in the city of Lhokseumawe as a sample. Primary data or direct use of a questionnaire were used to obtain data in this study. Multiple linear regression analysis was employed as the method of analysis. The f test and the t test are the hypothesis tests used in this investigation.